The Paradox of Secularization: The Dynamics of Religious Moderation and Identity Politics in Indonesia - Haikal Ramli, Muhammad (Social Impact Journal, 2025)
Indonesia, as the country with the greatest religious diversity in the world, faces complex challenges in balancing secular and religious values in national life. The phenomenon of secularization that has developed in the modern era has not necessarily eliminated the role of religion in the public sphere, but rather created a paradox in which religion continues to exert a strong influence on socio-political dynamics. This study aims to analyze the paradox of secularization in the context of religious moderation and identity politics in Indonesia, as well as why religious moderation policies have not been fully effective in curbing identity politics. This study is a descriptive study with a qualitative approach. Data collection methods were carried out through library research, namely by compiling secondary data from various relevant written sources. Secularization in Indonesia has different characteristics from secularization in the Western world. Identity politics has become a central phenomenon in contemporary democratic dynamics, where religion is often mobilized as a tool for legitimizing power. This situation creates a non-linear form of secularization—not leading to the separation of religion and state, but rather to the consolidation of religious-based political power. The Indonesian government, through the Ministry of Religion, formulated the Moderate Religion Policy in 2019 as a response to the escalating intolerance and polarization of religious identities in the public sphere. The implementation of Religious Moderation still faces various structural challenges that hinder its effectiveness. To strengthen religious moderation, a comprehensive approach is needed that involves political system reform, strengthening digital literacy, and internalizing inclusive values at the community level.